Alumina as a Support and Catalyst for the Synthesis of Benzothiazoles in Solvent‐free Condition. Issue 6 (11th March 2013) - Ding, Mei‐Fang; Chen, Chia‐Pei; Lin, Shaw‐Tao
Abstract Arylbenzothiazole (4) and benzothiazolylcoumarins (5) were prepared by the condensation of 2‐aminothiophenol (1) and hydroxybenzaldehydes (2) and 3‐ethoxycarbonylcoumarinnin (3), respectively, in solvent‐free condition. Of the solid support used, γ‐Al2O3 demonstrated the best activity. A linear regression line obtained from correlation between relative formation rate and Hammett constants with slope of 0.653 suggested that this condensation process is less sensitive to the substituents on the phenyl ring due to low efficacy of polarization in the solid state. In general, good yields (>80% yield) were obtained for the formation of 4. Conversely, yields of 5 were poor, because of γ‐Al2O3 catalytic decomposition of 3 to form 2 (without P2O5) and coumarin (with P2O5).